A Multiprocess Item Response Model for Not-Reached Items due to Time Limits and Quitting. (June 2020) - Ulitzsch, Esther; von Davier, Matthias; Pohl, Steffi
So far, modeling approaches for not-reached items have considered one single underlying process. However, missing values at the end of a test can occur for a variety of reasons. On the one hand, examinees may not reach the end of a test due to time limits and lack of working speed. On the other hand, examinees may not attempt all items and quit responding due to, for example, fatigue or lack of motivation. We use response times retrieved from computerized testing to distinguish missing data due to lack of speed from missingness due to quitting. On the basis of this information, we present a new model that allows to disentangle and simultaneously model different missing data mechanisms underlying not-reached items. The model (a) supports a more fine-grained understanding of the processes underlying not-reached items and (b) allows to disentangle different sources describing test performance. In a simulation study, we evaluate estimation of the proposed model. In an empirical study, we show what insights can be gained regarding test-taking behavior using this model.